The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.psychsport.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of situational costs and benefits on projected doping likelihood

Abstract: Objectives: Our primary aim was to compare the influence of a range of situational factors (costs and benefits) on projected doping likelihood in hypothetical situations. A secondary aim was to examine whether doping likelihood was influenced by personal social cognitive factors implicated in the regulation of ethical behavior by Bandura's (1991) theory of moral thought and action and Aquino and Reed's (2002) model of moral identity. Design: Using a cross-sectional design, projected doping likelihood was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 37 publications
(93 reference statements)
4
34
1
1
Order By: Relevance
“…A series of Wilcoxon Signed Rank Tests indicated that cheating was more likely when the chance of being caught was 10% than both ACHIEVEMENT GOALS AND CHEATING 16 50%, Z = 1.90, p = .05, and 90%, Z = 3.50, p = .001, and more likely for 50% than 90%, Z = 2.53, p = .01. The current evidence showing that greater probability of being caught was associated with lower cheating likelihood, is compatible with studies showing that the likelihood of doping in hypothetical situations is lower when the probability of being detected is increased (Huybers & Mazanov, 2012;Ring, et al, 2018).…”
Section: Resultssupporting
confidence: 90%
“…A series of Wilcoxon Signed Rank Tests indicated that cheating was more likely when the chance of being caught was 10% than both ACHIEVEMENT GOALS AND CHEATING 16 50%, Z = 1.90, p = .05, and 90%, Z = 3.50, p = .001, and more likely for 50% than 90%, Z = 2.53, p = .01. The current evidence showing that greater probability of being caught was associated with lower cheating likelihood, is compatible with studies showing that the likelihood of doping in hypothetical situations is lower when the probability of being detected is increased (Huybers & Mazanov, 2012;Ring, et al, 2018).…”
Section: Resultssupporting
confidence: 90%
“…To our knowledge, no study has examined the relative strength exerted by the different mechanisms on doping by athletes (cf. Ring, Kavussanu, Simms, & Mazanov, 2018), or indeed any form of cheating or antisocial behavior in sport. To improve our understanding of the moral disengagement-doping relationship, we used an experimental design to compare the effects of six moral disengagement mechanisms on doping likelihood in hypothetical situations.…”
Section: Social Cognitive Theory Of Moral Thought and Actionmentioning
confidence: 99%
“…65 Consecuentemente, una posición favorable o desfavorable ante el dopaje deportivo incluiría la evaluación de amenazas, el examen de beneficios, la moralidad, la legitimidad en las pruebas de detección de drogas, la opinión de un grupo de referencia y los rasgos de personalidad. [66][67][68] Una manera de demostrar el poder predictivo de la personalidad en relación con el dopaje, es la propuesta de la Tríada Oscura, en la cual se supone que los rasgos de personalidad que más influyen en las actitudes frente al dopaje son el maquiavelismo (manipulación a otras personas), el narcisismo (visión exagerada de sí mismas y autocomplacencia) y la psicopatía (impulsividad, poca empatía por los demás y agresividad). 69 • La categoría 2.…”
Section: Resultados Y Análisisunclassified